Análise da resistência à fadiga flexural de instrumentos fabricados com a tecnologia CM após ensaios de flexão e ciclos de esterilização - Luiza Cruz Guimarães (2016)
The use of Controlled Memory technology involving the heat treatment of machined NiTi instruments is among the new strategies manufacturers have developed to improve files fatigue resistance and flexibility. The aim of this study was to evaluate the shape recovery capacity and maintenance of mechanical properties of Hyflex CM (HF; Coltene/Whaledent, USA) and Typhoon CM (TYP; Clinicians Choice Dental Products, USA) after being submitted to bending at 45°, sterilization and fatigue stresses. Ten instruments from each brand were submitted to the 45° bending test, according specification ISO 3630-1, autoclaved at 134°C for 20 minutes and photographed with a high resolution camera and with magnification to check whether all files have returned to their original shape. The images were analyzed in the software Image J 1.48V. In order to reproduce the clinical practice, five bending cycles were alternated with sterilization cycles. The average number of cycles until failure (Nf) were obtained for new instruments and instruments submitted to bend and sterilization in a bench device that simulates a curved canal. Both brands presented similar values of bending moments at 45º (Mb45) (p=0,239). A decrease in this values were verified after the five cycles of bending and sterilization, however only statistically relevant for HF instruments (p= 0,005). When submitted to sterilization, all HF instruments recovered their original shape. On the other hand, a significant number of TYP instruments were shown to be plastically deformed (p= 0,000) with an average residual deformation of 2,7°. TYP instruments submitted to five cycles of bending and sterilization presented a statistically significant decrease in their Nf (p=0,006), which did not occur to HF instruments (p=0,825). The two types of instruments tested in this study, although referenced as CM instruments, responded differently to thermal treatments applied during the manufacturing process and presents distinct shape recovery capacity and fatigue resistance.